Sources of the origin of national idea of the sovereign Republic of Kazakhstan (on the material of humanitarian discourse of the Leader of the nation – N. A. Nazarbayev) (Eurasian Journal of Philology Science and Education, 2016)
Article is devoted to a problem of formation of national idea of thepeople, the state. In it the humanitarian discourse of the president of theRepublic of Kazakhstan N.A. Nazarbayev, in particular his book «WorldEpicentre» (2001) is considered. In this regard such terms and their majorimportances as the nation, ethnos, national idea, a humanitarian discourse,etc. are studied. Article purpose – to show on material of the publicistictext as the national idea of the Kazakh people arose, in general the sovereignstate of the RK. As illustrative material fragments from the specifiedbook of the Leader of the nation in which information on the terminationof tests of the nuclear weapon in the territory of RK and refusal (1991-1999) of it is in detail stated are represented. For achievement of a researchobjective, complex selection from of the text of individual author’s maxims,their description and systematization were used. Results of the analysiscan be used on classes in the lingvostilistic analysis of a humanitariandiscourse for students and undergraduates of philological specialists.
Keywords: national idea; humanitarian discourse; nation; ethnos; author’s maxims.